Rac1 signalling modulates a STAT5/BCL-6 transcriptional switch on cell-cycle-associated target gene promoters - Barros, Patricia (2012)
Gene expression depends on binding of transcriptional regulators to gene promoters, a process controlled by signalling pathways. The transcriptional repressor BCL-6downregulates genes involved in cell cycle progression and becomes inactivated following phosphorylation by the Rac1 GTPase activated protein kinase PAK1.Interestingly, the DNA motifs recognized by BCL-6 and STAT5 are similar. Because STAT5 stimulation in epithelial cells can also be triggered by Rac1 signalling, weasked whether both factors have opposing roles in transcriptional regulation and whether Rac1 signalling may coordinate a transcription factor switch. We usedchromatin immunoprecipitation to show that active Rac1 promotes release of the repressor BCL-6 while increasing binding of STAT5A to a BCL-6-regulated reportergene. We further show in colorectal cell lines that the endogenous activation status of the Rac1/PAK1 pathway correlated with the phosphorylation status of BCL-6and STAT5A. Three cellular genes (cyclin D2, p15INK4B, SUMO1) were identified to be inversely regulated by BCL-6 and STAT5A and responded to Rac1 signalling withincreased expression and corresponding changes in promoter occupancy. Together, our data show that Rac1 signalling controls a group of target genes that arerepressed by BCL-6 and activated by STAT5A, providing novel insights into the modulation of gene transcription by GTPase signalling.